Combined Volar T-Plate and Dorsal Pi-Plate for Distal Radius Fractures: A Consecutive Series of 80 AO type C2 and C3 Cases - Sagerfors, Marcus; Bjorling, Patrik; Niklasson, Johan; Pettersson, Kurt (Journal of Wrist Surgery, 2019)
Background The distal radius fracture (DRF) is the most common fracture among adults. In recent years, there has been a shift toward volar locking plates in the treatment of DRFs, and this shift has taken place with a low degree of evidence.Question/purposes Can combined volar T-plating and dorsal pi-plating of AO type C fractures yield a good functional and radiographic outcome 1 year postoperatively?Patients and Methods In a retrospective cohort study, we evaluated 102 consecutive patients operated with combined dorsal and volar plating, of whom 80 completed the 1-year follow-up. The DRFs were operated between 2012 and 2013. All cases were AO type C2 and C3 fractures. The primary outcome was functional scoring including radiographic examination. Secondary outcome measures included range of motion, visual analog scale (VAS) pain scores, and hand grip strength.Results The median Batra radiographic score was 84.5. Wrist extension was 74% of the uninjured side, flexion was 70%, pronation was 94%, and supination was 90%. The Patient-Rated Wrist Evaluation score was 21 points, and the Disabilities of the Arm, Shoulder, and Hand score was 19.4 points. VAS pain scores were 0 at rest and 3 during activity. Hand grip strength was 80% of the uninjured side. Radiographic outcome did not correspond to a patient-reported outcome. Hardware removal was performed in 15/80 cases.Conclusions We conclude that a good outcome can be expected after combined dorsal and volar plating of DRFs. Radiographic outcome is not necessarily associated with functional outcome 1 year postoperatively. The rate of hardware removal was acceptable.Level of Evidence III
Keywords: distal radius; fracture; plating